2017
DOI: 10.1097/ico.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy Reveals Corneal Reinnervation After Treatment of Neurotrophic Keratopathy With Corneal Neurotization

Abstract: Corneal neurotization restores corneal sensation by reinnervating the stromal and subbasal layers of the cornea. In doing so, corneal neurotization may halt the process of NK and prevent further visual loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 10 publications
4
47
0
1
Order By: Relevance
“…Our results provide further evidence that nerve fibers innervate the corneal epithelium after corneal neurotization and improve ocular surface health. These results compliment the clinical studies performed in patients undergoing corneal neurotization, [21][22][23][24][25][26] and our animal model provides a means of further investigating corneal neurotization to elucidate by what mechanism corneal neurotization improves corneal epithelial integrity and healing after injury. These findings will greatly contribute to our understanding of corneal neurotization and support the use of corneal neurotization as a treatment for NK.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results provide further evidence that nerve fibers innervate the corneal epithelium after corneal neurotization and improve ocular surface health. These results compliment the clinical studies performed in patients undergoing corneal neurotization, [21][22][23][24][25][26] and our animal model provides a means of further investigating corneal neurotization to elucidate by what mechanism corneal neurotization improves corneal epithelial integrity and healing after injury. These findings will greatly contribute to our understanding of corneal neurotization and support the use of corneal neurotization as a treatment for NK.…”
Section: Discussionsupporting
confidence: 84%
“…Several techniques of corneal neurotization have been described. [21][22][23][24][25][26] Neurotization was performed in our model by using the contralateral ION via two autografts, similar to the technique described by Elbaz et al 21 The contralateral ION was used, as it is robust in the rat, and a contralateral donor permitted the confirmation with retrograde labeling that reinnervation of the cornea was derived from the contralateral donor nerve. Because each graft measured approximately 30 mm in length, the surgical procedure to place the grafts was performed prior to stereotactic ablation of the ophthalmomaxillary nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Interpositional nerve graft techniques coapted to a healthy donor nerve: A–F, Elbaz et al ,49 Bains et al ,50 Weis et al ,59 Fung et al 89; and direct nerve transfer (G, Terzis et al ,48 Allevi et al ,53 Ting et al ,57 Leyngold et al— supraorbital nerve only56; H, Jacinto et al 54; I, Professor Gennaro (personal communication, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fung et al 89 published recently their results of two cases where they showed the growth of corneal nerves after corneal neurotisation. To the best of our knowledge, this is the first report in the literature of using IVCM in assessing corneal nerves after corneal neurotisation.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo confocal microscopy has shown that this nerve transfer technique can successfully reinnervate the cornea [24]. Initial small series have shown that all operated patients have had improvement in corneal sensation postoperatively [25,26].…”
Section: Corneal Sensationmentioning
confidence: 99%